2008
DOI: 10.1253/circj.72.44
|View full text |Cite
|
Sign up to set email alerts
|

Fat and Fiber Consumption are Associated With Peripheral Arterial Disease in a Cross-Sectional Study of a Japanese-Brazilian Population

Abstract: eripheral arterial disease (PAD) is a severe atherosclerotic complication of diabetes mellitus and hypertension with a deleterious impact on the quality of life. Walking intolerance and amputation are major problems for subjects with PAD. Moreover, this is associated with an increased cardiovascular and cerebrovascular morbidity and mortality. People with PAD are more than 4 times likely to die of any cause over 2 years from diagnosis than those without this condition. [1][2][3][4] PAD may be identified non-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Despite the recognition of the limitations in the direct comparison between findings from the current study and those of other researchers (particularly because of the different age structures in these population groups and the different approaches used), one can state that the prevalence of hyperuricemia detected among Japanese-Brazilians (35.3%) was higher than described in international studies 11,35,36 . As identified in previous publications by the JBDSG 19,21,33,34 , this community also displays high rates of co-morbidities associated with hyperuricemia, thus characterizing high risk for cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Despite the recognition of the limitations in the direct comparison between findings from the current study and those of other researchers (particularly because of the different age structures in these population groups and the different approaches used), one can state that the prevalence of hyperuricemia detected among Japanese-Brazilians (35.3%) was higher than described in international studies 11,35,36 . As identified in previous publications by the JBDSG 19,21,33,34 , this community also displays high rates of co-morbidities associated with hyperuricemia, thus characterizing high risk for cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 68%
“…In this community, along with the glucose intolerance "epidemic", studies have also shown high prevalence rates for dyslipidemia, arterial hypertension, metabolic syndrome, and central obesity, all of which at higher rates than in the overall Brazilian population or in Japanese living in Japan 19,21,33,34 . In Brazil, there are no available data from population-based epidemiological studies on the occurrence of altered serum uric acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral artery disease patients also had elevated serum levels of triglyceride compared with those without PAD. [17][18][19] A higher serum triglyceride level has been shown to be associated with a low ABI value in asymptomatic patients between 50 and 70 years of age. 20 Our results also identified higher serum total cholesterol and higher triglyceride levels in the low ABI group, and the serum triglyceride level was negatively correlated with the ABI value for renal transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Salvo et al 37 (2009) stated that the Nikkei diet, irrespective of macrovascular disease, was composed by 54% carbohydrates, 14% proteins and 32% lipids in relation to their daily calorie intake. In another publication, referring to the same study, 13 the authors verifi ed that higher consumption of total fats was signifi cantly linked to peripheral arterial disease. This link was corroborated by Freire et al 8 (2005), who verifi ed signifi cantly higher lipid intake in men with metabolic syndrome than in those without this disorder.…”
Section: Studies With Japanese-braziliansmentioning
confidence: 91%